Les élites de Saint-Domingue au XVIIIe siècle : réflexions méthodologiques - Zélie Navarro-Andraud (Caravelle)
Essential to all types of research, the choice of a methodological procedure must be relevant to the discipline, the theme and the aims of the study. Within this perspective, this attempt to elaborate a thought pretends to be a presentation, step by step, of a methodological procedure, from the beginnings of the research till the examination and critical analysis of materials and sources. Trying to respond to such ambition, this article presents a specific method : prosography. Indeed, the object here is not to display a survey of the multiple methods of analysis in human sciences, but to present the complete precision of a procedure and of a stream of thought by basing the arguments upon the case of a precise research subject.